MANAJEMENT OF INSOMNIA IN GERIATRIC PATIENTS - Devi Larayanthi, Cokorda Istri (E-Jurnal Medika Udayana; vol 2 no5(2013):e-jurnal medika udayana, 2013)
Sleep is an unconscious condition that is relatively more responsive to internal stimuli. Insomnia is a sleep disorder with characteristic difficulty of initiating sleep or difficulty in maintaining sleep. Insomnia is divided into 2 primary insomnia and secondary insomnia. Conection with age, the function of organs in the body decreases. So that geriatric patients are susceptible to illnesses, especially insomnia. Many of the causes of insomnia in geriatric mental disorders, psychiatric, general medical conditions, medications, certain substances, and others. Management of insomnia in geriatric patients were divided into 3 method: 1) manage underlying cause, 2) nonpharmacological therapies such as cognitive behavior therapy (CBT), and 3) pharmacological therapies such as benzodiazepine and non-benzodiazepine that eszopiclone and Ramelteon. Pharmacological treatment in geriatrics should follow the rule "start low, go slow", starting dose of ½ of the adult dose, and its use in the short term.
Keywords: insomnia, geriatric